Landasan Hukum Pertimbangan Hakim Dalam Memutuskan Perkara Hak Asuh Anak (Hadhanah) Di Pengadilan Agama Sleman Yogyakarta Tahun 2017 - Haryati, Sri (Universitas Islam Indonesia, 2020)
Today, marriage is an engagement between a male and a femake to undergo the life as a couple, building a household, and regenerating in accordance with sharia provisions. However, in marriage a few problems might often occur and are caused by various things leading to a divorce and positioning the children as the victim of divorce occurred between their parents. Children have to know their parents’ problems and must follow one of their parents for care. In this research, the researcher used a field research method by taking data samples and interviews with the Judge in Religious Court Sleman appointed by the head of the Sleman Religious Court. Legal considerations in coping with the case of child custody right need to be learned in which the judicial authorities are expected to result in the qualified decision, so that the judges in Religious Court Sleman in resolving the cases will be based upon the positive legal rules and Islamic laws applied in Indonesia. However, the judges of Religious Court Sleman judge attempted (ijthad) to say that case of custody right is solely for the children in the future to prevent any disadvantages. Based on the data obtained in field, the judge decision in Religious Court Sleman in 2017 related to custody right case (hadhanah) was totally given for the mother based on a number of judgements of the judges.